The quality of educational services in the Saudi schools in Kuala Lumpur, Paris and Rome - Al-Towaijri, Hailah Mandeel (Institute of Education, IIUM, 2011)
This study examined the extent at which the quality of teaching services was offered by the Saudi schools overseas to their students in Kuala Lumpur, Paris and Rome according to guardians, teachers and students. It assessed the effectiveness of the criteria applied in improving the standard of the Saudi schools, their performance and analyzed the extent of the influence of demographic studies on the quality of teaching services offered by these schools according to the guardians, teachers and students. Moreover, the study investigated the importance of each underlying factor that influences respondents' perceptions of the Total Quality Criteria of their schools and determined the most important determinants of the perceived Quality Educational Services according to the guardians, teachers and students. The sample of the study comprised 120 students, 88 guardians and 65 teachers from the three schools. This study was a survey research which used two types of questionnaires namely; SERVQUAL and Total Quality Criteria instruments to collect the data. In terms of analysis, the data were analyzed using Confirmatory Factor Analysis (CF A) to confom the items' goodness of fit and determine the underlying or dominant factors that greatly influenced Total Quality Management Criteria and Educational Services. Additionally, MANOV A was used to identify the significant differences between demographics and the study variables. The data were also analyzed descriptively to know the extent at which the criteria and services were sustained in the three schools. Finally, the results of the study according to descriptive analysis showed that, material capabilities may not be so important factor to improve the standard of the schools from the point of views of the students, guardians and teachers as long as the rest factors are maintained. Thus, students, parents and teachers seemed to agree that the whole factors of the total quality criteria were the most important factors to develop the schools. In terms of Quality Educational Services, the results showed that most of the services were maintained and provided. From the same analysis, the results of MANOV A showed an insignificant relationship of all the demographic variables with the study variables. PCA and CF A results showed that, Staff, Material Capabilities, Teacher, Information Technology and Efficiency factors could contribute to the quality of educational services provided by the schools and also could be used as factors to improve the total quality of the schools. As a recommendation, Saudi schools management should be capable of providing good materials for learning activities, advanced information technology, facilities, well equipped playgrounds and, have a good relationship with the community outside the schools.